2015
DOI: 10.1111/jcpp.12384
|View full text |Cite
|
Sign up to set email alerts
|

Implicit sequence learning in juvenile anorexia nervosa: neural mechanisms and the impact of starvation

Abstract: Our data suggest that the impaired implicit learning observed in adolescent AN patients before weight gain is a state-related dysfunction that normalises with weight gain. Thus, implicit learning deficits do not appear to represent a predisposition towards developing AN; rather, these deficits should be considered when planning psychotherapeutic interventions for acute AN. Reduced thalamic activation during the acute stage of AN may indicate a starvation-induced dysfunction of the neural circuitry that is invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 49 publications
1
30
0
Order By: Relevance
“…Our results come from a behavioral task, and do not directly assess brain function. Nonetheless, the findings are consistent with other studies that have investigated forms of striatal-based learning in AN (Firk et al, 2015;Lawrence et al, 2003;Shott et al, 2012). Additionally, previous studies using the Acquired Equivalence task in patients with Parkinson's disease, who are known to have striatal dysfunction, have shown a pattern of learning impairment similar to that seen in the present study (Myers et al, 2013), suggesting that striatal function may be impaired in AN.…”
Section: Discussionsupporting
confidence: 92%
“…Our results come from a behavioral task, and do not directly assess brain function. Nonetheless, the findings are consistent with other studies that have investigated forms of striatal-based learning in AN (Firk et al, 2015;Lawrence et al, 2003;Shott et al, 2012). Additionally, previous studies using the Acquired Equivalence task in patients with Parkinson's disease, who are known to have striatal dysfunction, have shown a pattern of learning impairment similar to that seen in the present study (Myers et al, 2013), suggesting that striatal function may be impaired in AN.…”
Section: Discussionsupporting
confidence: 92%
“…There are a number of possible explanations for this finding. It may be that the elevation in ASD traits measured at assessment, when young people with restrictive EDs are in a state of starvation, reflects the impact of a lack of adequate nutrition on social, emotional and cognitive processes which results in social withdrawal, reduction in communication and restricted or repetitive behaviours (Pender et al, 2014;Firk et al, 2015), rather than a neurodevelopmental disorder per se. Alternatively, it has been suggested that the tools currently used to diagnose ASD do not adequately identify early indicators of difficulty in girls who may have a qualitatively different presentation to that of boys (Halladay et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that ASD and anorexia nervosa (AN) are related disorders which share common neuropsychological features (Gillberg & Rastam, 1992;Oldershaw, Treasure, Hambrook, Tchanturia, & Schmidt, 2011;Lang, Lopez, Stahl, Tchanturia, & Treasure, 2014). However, the clinical and neuropsychological ASD traits observed in AN may instead reflect the impact of starvation on the brain (Pender, Gilbert, & Serpell, 2014;Firk et al, 2015). It may also be that common clinical and research practices under detect or underdiagnose ASD in females (Halladay et al, 2015) and that a proportion of those who present with AN had a pre-existing undiagnosed ASD.…”
Section: Introductionmentioning
confidence: 99%
“…)Viewing images of body checkingSuda et al, 2013 [28]AN = 20HC = 15DSM-IV15.7 (1.0)27.0 (7.5)Investigate brain activation to images of body checkingReduced activation of the anteromedial prefrontal cortex and fusiform gyrusViewing images of faces and houses at different spatial frequenciesLi et al, 2015 [30]AN-REC = 15HC = 15BDD = 15DSM-IV20.4 (1.6)23.6 (3.5)Investigate visual and visuospatial processing in AN and body dysmorphic disorder (BDD)Both groups had increased activation in secondary visual processing regions and dorsal visual streamNeuropsych functionsEmbedded figures testFonville et al, 2013 [31]AN = 35HC = 35DSM-IV16.0 (1.6)23.0 (9.0)Investigate neural patterns of activity in response to tests of central coherenceReduced activity in the precuneus, increased activation in the fusiform gyrusStop-signal taskWierenga et al, 2014 [33]AN = 11HC = 12DSM-IV16.9 (1.5)16.0 (2.0)Explore inhibitory processing in ANInhibitory processing was related to reduced activity in dorsal anterior cingulate cortex, middle frontal gyrus, posterior cingulate cortex. Error processing was related to reduced activity in the middle frontal gyrus and posterior cingulate cortexWisconsin card sorting test (WCST)Sato et al, 2013 [35]AN = 15(AN-R = 9)(AN-BP = 6)HC = 15DSM-IV14.6 (1.5)23.0 (7.0)Evaluate brain activity in patients with AN while performing the WCSTReduced activity in the ventrolateralprefrontal cortex and parahippocampal cortex during set shifting in all AN patients.Serial reaction timeFirk et al, 2015 [36]AN = 19HC = 20DSM-IV15.2 (1.5)15.9 (1.5)Examine implicit learning in ANReduced activity in the thalamusLetter n-back taskLao-Kaim et al, 2014 [37]AN = 31HC = 31DSM-IV16.0 (1.6)23.0 b Investigate the effect of increasing verbal working memory task difficulty on cortical functioningNo significant differencesWorking memory task, not emotional stimuliCastro-Fornieles et al, 2010 [17]AN = 14(Male/female:2/12)HC = 14DSM-IV14.9 (2.1)15.0 (1.7)Investigate brain activation during a non-emotional working memory taskIncreased activation in superior parietal lobule and inferior temporal gyrusGo/no-go task…”
Section: Main Textmentioning
confidence: 99%
“…Inhibitory processing was associated with reduced activity in the dorsal anterior cingulate cortex, middle frontal gyrus and posterior cingulate cortex [33], and activation patterns were found to be dependent on the type of stimuli used in the task [34]. Performance on a set-shifting task was linked to reduced activation in the prefrontal cortex and parahippocampal cortex [35] whereas implicit learning was linked to reduced activity in the thalamus [36]. One study of working memory found increased activation in the superior parietal lobule and inferior temporal gyrus [17] while another found no differences between patients and controls [37].…”
Section: Main Textmentioning
confidence: 99%